Penyuluhan Kesehatan Upaya Pencegahan Penyakit Infeksi HIV/AIDS Pada Keluarga Kelurahan Batua Wilayah Kerja Puskesmas Batua Makassar - Rachmat Ramli; Adi Hermawan (Jurnal Pengabdian Ilmu Kesehatan, 2022)
One of the main contributors to the global spread of HIV is migrant workers. The purpose of this community service is to determine whether the community's efforts, especially at the Batua Health Center, prevent HIV/AIDS in families at risk of HIV/AIDS. This research was conducted with a cross-sectional design with a quantitative approach. The study population was all patients who visited Batua Health Center, and 94 samples were taken. Data collection was carried out in August-September 2020. Data analysis included univariate and bivariate analysis. The results of this study indicate that individual characteristics, adolescent behavior p = 0.486, sources of information p = 0.680, knowledge p = 0.003, and attitudes p = 0.589 relationship with adolescent behavior toward HIV/AIDS. Knowledge with p = 0.865 shows no significant relationship between knowledge and risk behavior toward HIV/AIDS.